2014
DOI: 10.9790/5736-07731525
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Distribution of Inorganic Ions in Rainwater of Jos and Bukuru Metropolis, Plateau State, Nigeria

Abstract: Rainwater samples were collected during the raining season from five sites within Jos and Bukuru metropolis from April to October, 2002 and 2007. Eighty-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…While no ISSN: 2581-5059 www.mjbas.com 30 significant correlation was observed between the other pairs. These implied that the pairs either have the same source of chemical species (Nangbes et al, 2019;Nangbes et al 2014;Ashraf et al, 2012 Generally, the ponds were shown to be polluted with heavy metals thus the risk of bioconcentration and bioaccumulation of these heavy metals in the aquatic lives, thus endangering human health directly when consumed or through the food chain.…”
Section: Resultsmentioning
confidence: 99%
“…While no ISSN: 2581-5059 www.mjbas.com 30 significant correlation was observed between the other pairs. These implied that the pairs either have the same source of chemical species (Nangbes et al, 2019;Nangbes et al 2014;Ashraf et al, 2012 Generally, the ponds were shown to be polluted with heavy metals thus the risk of bioconcentration and bioaccumulation of these heavy metals in the aquatic lives, thus endangering human health directly when consumed or through the food chain.…”
Section: Resultsmentioning
confidence: 99%